Centre For Graduate Studies: Graduate Programs 2002 2003/ Centre for Graduate Studies, UiTM - UiTM, Centre for Graduate Studies (Centre for Graduate Studies, UiTM, 2002)
UiTM takes pride in its establishment as on of the premier institutions of higher education in the country. Although the history of UiTM dates back to 1956, the genesis and growth of the Centre for Graduate Studies (CGS) can be traced to April 1997.